Study on Properties of Energetic Plasticizer Modified Double‐Base Propellant. Issue 11 (19th October 2021) - Zou, Xiaobin; Zhang, Wenguo; Zhang, Zehao; Gu, Yongjun; Fu, Xiuchong; Ge, Zhen; Luo, Yunjun
Abstract: To improve the low‐temperature mechanical properties of double‐base propellants, the effects of three energetic plasticizers (geminal dinitro aldehyde acetal plasticizer, azido‐terminated glycidyl azide polymer, and ester‐terminated glycidyl azide polymer) on the low‐temperature mechanical properties of nitrocellulose (NC)/nitroglycerin (NG) propellant were studied firstly in this article. It was found that azido‐terminated glycidyl azide polymer (GAPA) was the most effective plasticizer to improve the low‐temperature mechanical properties of NC/NG propellant. Then the effects of GAPA on the low‐temperature static tensile mechanical properties, thermal stability, dynamic thermomechanical properties, density, and heat of detonation of fully‐formulated double‐base propellant with ETPE were studied. It was found that the double‐base propellant with 1 % GAPA had the best comprehensive performance, and its maximum tensile strength and elongation at break at low temperature (−40 °C) were 56.16 MPa and 10.63 %, respectively. The elongation at break was increased by 10.2 % compared to the double‐base propellant without an energetic plasticizer. Meanwhile, the correlation between dynamic and static mechanical properties of the double‐base propellant with 1 % GAPA was also studied, and the relationship between the dynamic storage modulus and the static tensile strength was obtained. Abstract :